The trend of phylogenetic and epitope variations of SARS-CoV-2 Omicron sub-lineages in Iran - Shabani, Mehdi; Nejati, Ahmad; Yavarian, Jila; Sadeghi, Kaveh; Zadheidar, Sevrin; Ahmadi, Akram Sadat; Ghadirali, Monire; Zebardast, Arghavan; Abedi, Adel; Najmi, Mohammad Hossein; Shafiei-Jandaghi, Nazanin-Zahra; Mokhtari-Azad, Talat (Frontiers in Microbiology, 2025)
IntroductionSevere acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been a significant public health issue worldwide in recent years. The most recently circulating variant of SARS-CoV-2, Omicron, and its rapid evolution into various sub-lineages have raised concerns regarding the effects of the immunity on the virus epitopes, in the human population. The present study evaluated and compared these important variations among different Omicron sub-lineages in Iran.MethodologyFrom October 2023 to August 2024, high coverage whole genome sequences of 49 SARS-CoV-2 strains were subjected to phylogenetic analysis and evaluation of B cell, CD4+, and CD8+ T cell epitopes in Iran National Influenza Centre.ResultsThe phylogenetic tree exhibited eight Nextstrain clades (21L, 22F, 23B, 23H, 23D, 24A, 24B, and 24C) in 48 studied strains, and one recombinant strain (XDK.1). The evaluation of B cell, CD4+, and CD8+ T cell epitopes in all studied strains revealed 31, 65, and 78%, of conservation, respectively. The low B cell epitopes conservation rate among Omicron sub-lineages underscored the escaping from neutralizing humoral immunity. T cell epitopes of the SARS-CoV-2 were considerably preserved across major Omicron sub-lineages. Conservation levels varied based on the epitope class (higher for CD8+ vs. CD4+), protein (higher for non-spike vs. spike), and clades (higher for 21L, 22F, 23B, 23H, 23D, and 24B vs. 24A and 24C).ConclusionHerein, the increased conservation of CD8+ epitopes compared to CD4+ and B cell epitopes is probably attributable to the shorter length of the peptides associated with CD8+ epitopes. The high rate of T-cell epitopes conservation in non-spike proteins among different sub-lineages of the Omicron in this study highlighted the importance of cell-mediated immunity and suggested that non-spike proteins might be more attractive targets for future SARS-CoV-2 vaccines.